2021
DOI: 10.3389/fimmu.2021.707468
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Safety and Potential Effect of 6B11-OCIK Adoptive Cell Therapy Against Platinum-Resistant Recurrent or Refractory Ovarian Cancer

Abstract: Ovarian cancer is a leading cause of death among gynecological malignancies, and novel therapies are urgently needed. Here we report preliminary findings on the potential safety and efficacy of 6B11-OCIK, an adoptive cell therapy of autologous T cells induced by the humanized anti-idiotypic antibody 6B11 minibody plus dendritic cells and cytokines, against platinum-resistant recurrent or refractory ovarian cancer in three patients. We found that 6B11-OCIK treatment was safe and well tolerated after five cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…Importantly, CTCs carry all or part of the genetic information of the primary tumor, which has made CTCs critical diagnostic markers and/or sources for tumor evaluation that aid in precision medicine. In our previous study, we used the SE-iFISH system with probes for CEP8 and CA125 or HE4 expression to identify CTCs [23]. This system is convenient for detecting the aneuploidy of Chr8, and the results indicated that among the 210 CTCs from 20 EOC patients, almost all CTCs showed Chr8 aneuploidy, which was consistent with single-cell sequencing and TCGA analysis.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Importantly, CTCs carry all or part of the genetic information of the primary tumor, which has made CTCs critical diagnostic markers and/or sources for tumor evaluation that aid in precision medicine. In our previous study, we used the SE-iFISH system with probes for CEP8 and CA125 or HE4 expression to identify CTCs [23]. This system is convenient for detecting the aneuploidy of Chr8, and the results indicated that among the 210 CTCs from 20 EOC patients, almost all CTCs showed Chr8 aneuploidy, which was consistent with single-cell sequencing and TCGA analysis.…”
Section: Discussionsupporting
confidence: 65%
“…We defined c-Myc amplification as ≥1.5 copies of c-Myc/CEP8 per cell and found that c-Myc amplification was associated with the pathological pattern, grade, lymphatic metastasis, and ER positivity (Table 3). Circulating tumor cells (CTCs) in peripheral blood were enriched by SE-iFISH, as described in our previous study [23]. A total of 210 CTCs were enriched from 20 EOC patients.…”
Section: Aneuploidy Of Chr8 Is Present In Eoc Tissues Cell Lines and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be helpful to improve the immune escape of ovarian cancer, especially for patients with recurrent ovarian cancer. An adoptive cell therapy of autologous T cells induced by a humanized anti-adiotypic antibody 6B11 minibody plus DCs and cytokines demonstrated preliminary safety and potential clinical efficacy in a phase I clinical trial of platinum-resistant recurrent or refractory ovarian cancer (144). A phase II study of allogeneic NK cell therapy for recurrent ovarian cancer showed suboptimal efficacy, and Treg cells were revealed to represent a treatment barrier (157).…”
Section: Supplementation or Deprivation Of Metabolismmentioning
confidence: 99%